Local linkage, external economies and the ironfoundry industry of the West Midlands and East Lancashire Conurbations - Taylor, M.J. (Regional studies, 1973)
Taylor M. J. (1973) Local linkage, external economies and the ironfoundry industry of the West Midlands and East Lancashire Conurbations, Reg. Studies 7, 387-400. The paper attempts to measure the impact of local external economies on the material linkages of ironfoundries in the West Midlands and East Lancashire conurbations. To facilitate measurement of this impact a simple interaction model is employed to generate hypothetical linkage patterns with which observed linkage patterns are compared. The results of such comparisons suggest that the impact of local external economies is most marked in relation to ironfoundry sales rather than ironfoundry purchases, and that this impact is greater in East Lancashire than the West Midlands. Viewed in the light of post war changes in the output of different types of iron casting and ironfoundry birth and death rates, these results suggest that the local external economies available to ironfounders are of a behavioural rather than a monetary nature.